Método de carga para banco de baterias em fontes ininterruptas de energia que busca garantir o estado de carga completa: corrente pulsada modificado - Cardoso, Renato Tavares (2015)
This Master s Dissertation is proposes the development of a charge management system of a bank of 16 lead-acid batteries with 7Ah load capacity, commonly used in Uninterruptible Power Supplies (UPS). This system aims to ensure that these batteries reach a full charge status faster than the conventional way. To this, it was chosen to make the modification of the pulsed current charging method, in order to reduce problems, such as elevation of bus voltage to return the energy to it, or dissipation of that energy in a resistance, resulting in lower system efficiency, inherent in the method taken as a basis when the battery power withdrawal interval occurs. For the development of the suggested charging system the static converter Full-Bridge Isolated with modulation Phase Shift was chosen. To implement the digital control as well as its practical development in the same laboratory the simplified modeling of this converter was made. The results of simulation and experimental to validate the method are presented.